Digestive enzymes activities in Oreochromis niloticus fed diet supplemented with recombinant growth hormone - Vinasyiam, Apriana; Suprayudi, Muhammad Agus; Alimuddin, , (Indonesian Society of Scientific Aquaculture (ISSA), 2016)
ABSTRACT The specific activity of the digestive enzymes, namely: pepsin, amylase, lipase, trypsin, and chymotrypsin were studied in Nile tilapia Oreochromis niloticus fed diet supplemented with recombinant Ephinephelus lanceolatus growth hormone (rElGH). The results showed that fish treated with rE1GH showed lower lipase and chymotrypsin specific activities (P>0.05), while the trypsin/chymotrypsin specific activity (T/C ratio) was found higher compared to control fish. Moreover, higher protein digestibility, higher protein retention and a lower ammonia excretion rate were measured for rE1GH treated fish. Oral rElGH administration enhanced Nile tilapia growth up to 20.04%, without affecting survival. This study suggested that rapid growth performance induced by rElGH was linked with T/C ratio rather than the specific activity of other digestive enzymes. Keywords: recombinant growth hormone, digestive enzyme, digestibility, Oreochromis niloticus ABSTRAK Aktivitas spesifik enzim pencernaan pepsin, amilase, lipase, tripsin, dan kemotripsin diamati pada ikan nila Oreochromis niloticus yang diberi pakan mengandung hormon pertumbuhan rekombinan ikan kerapu kertang Ephinephelus lanceolatus (rElGH)). Hasil menunjukkan bahwa ikan uji pada perlakuan rElGH memiliki aktivitas spesifik enzim lipase dan kemotripsin yang lebih rendah, sedangkan rasio tripsin/kemotripsin (rasio T/C) yang lebih tinggi dibandingan ikan kontrol. Kecernaan protein dan retensi protein bernilai lebih tinggi sementara laju ekskresi amonia bernilai lebih rendah pada ikan perlakuan. Pemberian rElGH secara oral mampu mempercepat laju pertumbuhan ikan nila hingga 20,04% tanpa memengaruhi kelangsungan hidup. Berdasarkan penelitian ini, dapat disimpulkan bahwa laju pertumbuhan cepat yang diinduksi oleh rElGH berhubungan dengan rasio T/C dibandingkan dengan aktivitas spesifik enzim pencernaan lain. Kata kunci: hormon pertumbuhan rekombinan, enzim pencernaan, kecernaan, Oreochromis niloticus